Głos dziecka w przedszkolu – między swobodą wypowiedzi a milczeniem - Anna Babicka-Wirkus; Maria Groenwald (Problemy Wczesnej Edukacji)
The article addresses the problems of presence and absence of child’s voice in kindergarten and their significance for the development of critically thinking entities/citizens. On the basis of our qualitative studies, two separate ways of perceiving the significance of nonadults’ voice in the early childhood education process have emerged. The first one, relating to the affirmation of free child expression, is typical for personal declarations of young educators. The second way is about practising children’s silence in kindergarten and it characterises the events described by aspiring teachers, witnessed during their professional practice. On this basis, we have identified the mechanism of inclusion and the mechanism of exclusion of child’s voice in kindergarten.